Efecto de la molienda vía húmeda en las propiedades físico-mecánicas y estructurales de baldosas cerámicas extruidas - Daniel Fernando Jurado-Pabuence; Camilo Andrés Alvarado-Gallo; Leonardo Cely-Illera; Jairo Cely-Niño; Keila Anteliz-Contreras; Claudia Vanessa Cely-Illera (Mundo Fesc)
Regionally, ceramic companies limit themselves to characterizing raw materials, without considering grinding methods and forming techniques, which will influence the final properties of the finished product. This article evaluates the comprehensive benefits of an extruded clay raw material during the beehive kiln firing stage, after having undergone a reconversion in the preparation method. The feasibility of industrially producing extruded ceramic floor and wall tiles using wet grinding was established, and the advantages of this grinding are demonstrated, achieving a comprehensive benefit, including improved resource utilization, increased quality, and maximum product profitability.